A national comparison of biochemistry and molecular biology capstone experiences. Issue 4 (14th July 2015) - Aguanno, Ann; Mertz, Pamela; Martin, Debra; Bell, Ellis
Abstract Recognizing the increasingly integrative nature of the molecular life sciences, the American Society for Biochemistry and Molecular Biology (ASBMB) recommends that Biochemistry and Molecular Biology (BMB) programs develop curricula based on concepts, content, topics, and expected student outcomes, rather than courses. To that end, ASBMB conducted a series of regional workshops to build a BMB Concept Inventory containing validated assessment tools, based on foundational and discipline‐specific knowledge and essential skills, for the community to use. A culminating activity, which integrates the educational experience, is often part of undergraduate molecular life science programs. These "capstone" experiences are commonly defined as an attempt to measure student ability to synthesize and integrate acquired knowledge. However, the format, implementation, and approach to outcome assessment of these experiences are quite varied across the nation. Here we report the results of a nation‐wide survey on BMB capstone experiences and discuss this in the context of published reports about capstones and the findings of the workshops driving the development of the BMB Concept Inventory. Both the survey results and the published reports reveal that, although capstone practices do vary, certain formats for the experience are used more frequently and similarities in learning objectives were identified. The use of rubrics to measure student learning is also regularly reported, but details about these assessment instruments are sparse in the literature and were not a focus of our survey. Finally, we outline commonalities in the current practice of capstones and suggest the next steps needed to elucidate best practices. © 2015 by the International Union of Biochemistry and Molecular Biology, 43(4):223–232, 2015.